Pressure dependence of the superconducting transition temperature of magnesium diboride. - Monteverde, M; Núñez-Regueiro, M; Rogado, N; Regan, K; Hayward, M; He, T; Loureiro, S; Cava, R (2001)
We studied the pressure and temperature dependence of the electrical resistivity of the superconducting compound magnesium diboride (MgB(2)). The superconducting transition temperature decreases monotonically with pressure, being parabolic or linear, depending on samples. The rate of decrease under pressure is higher than in conventional superconductors. We discuss our results in terms of the semimetallic character of the electronic band structure of MgB(2).